A clinical study of prevalence of gestational diabetes mellitus and associated risk factors at a tertiary care centre in Karnataka, India - S., Shridevi A.; Prabhudev, Prema; Bhovi, Madhusoodana R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Women with GDM are at increased risk for adverse obstetric and perinatal outcome .This study was undertaken to evaluate the prevalence of GDM using Diabetes in pregnancy study group India (DIPSI) criteria and associated risk factors in pregnant women. Methods: Universal screening for GDM was done in 200 pregnant women with estimated gestational age between 14 -18 weeks. They were given 75 gm oral glucose irrespective of meals. Diagnosis of GDM was made if 2 hr plasma glucose was ≥140, If plasma glucose is <140 then the test is repeated at 24-28 weeks. If normal, then the test is repeated at 32 weeks. If plasma glucose is <140 mg at 32 weeks, then they are classified as non –GDM group. Prevalence of risk factors like age ≥25, BMI ≥25, family history of DM, bad obstetric history, history of GDM and macrosomia were studied in GDM and non GDM group and results are statistically analysed. Results: The prevalence in this study was 11.5%. The prevalence was more in women with advanced age, high BMI, positive family history of DM, past history of GDM and macrosomia. Conclusions: The prevalence of GDM was found to be 11.5 % and its association with risk factors found to be significant. DIPSI diagnostic procedure is a simple, cost effective and evidence based test.